SYSTEMATIC REVIEW OF RISK FACTORS CONTRIBUTING TO MUSCULOSKELETAL DISORDERS (MSDs) AND INJURIES IN MILITARY PERSONNEL - Siti Nurhafizah Saleeza Ramlee; Hari Krishnan A/L Tamil Selvan; Megat Azman Megat Mokhtar; Nurhana Mohammad Rafiudin; Khairul Nizam, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This systematic literature review studies the occurrence and contributing factors of musculoskeletal disorders (MSDs) and injuries among military personnel. Musculoskeletal injuries (MSKIs) are a significant concern within military populations caused by the physically demanding nature of their respective duties, which often leads to high rates of disability and medical discharge. A comprehensive methodology was employed, involving systematic searches of electronic databases, including PubMed and Scopus, to identify peer-reviewed articles published between 2020-2024 that examined the occurrence of MSDs along with the psychological and physical risk factors contributing to these conditions, and the effectiveness of injury prevention and management strategies. Our findings reveal that the occurence of MSDs in military personnel is alarmingly high, with key risk factors identified across three themes: first, the prevalence and risk factors associated with MSDs indicate a strong correlation with the demands of military training and operational activities; second, psychological factors, including stress and mental health issues, along with physical risk factors like inadequate conditioning and repetitive movements, significantly contribute to the likelihood of injury; finally, effective injury prevention and management strategies, such as training programs and ergonomic assessments, holds a vital function in reducing the frequency and impact of MSDs. This review underscores the need for comprehensive interventions addressing both physical and psychological factors to mitigate the risks of MSKIs in military settings, ultimately enhancing the health and operational readiness of military personnel.